Arduino robotics - Warren, John-David (Technology in action series., 2011)
This book will show you how to use yourĂrduino to control a variety of different robots, while providing step-by-step instructions on the entire robot building process. You'll learn Arduino basics as well as the characteristics of different types of motors used in robotics. You also discover controller methods and failsafe methods, ănd learnÆhowÆto apply them to your project. The book starts withÆbasic robots and moves into more complex projects, includingă GPS-enabled robot, a robotic lawn mower, a fighting bot, and even a DIY Segway-clone. Introduction to the Arduino and other components needed for roboticsÆ Learn how to build motor controllers Build bots from simpleÆline-following and bump-sensorÆbotsÆtoÆmore complex robotsÆthat canÆmow your lawn, do battle, ŏr even take you for a ride Please note: the print version of this title is black & white; the eBook is full color.